Targeted cyber attacks: how to mitigate the increasing risk. Issue 1 (January 2020) - Bunker, Guy
Abstract : In the past year, it has felt as if cyber security breaches have rarely been out of the press, with more and more reports of organisations and individuals becoming victims of targeted attacks. Sainsbury's, Uber and Argos are just three examples of companies out of more than 100 who fell victim to this summer's Capital One breach. 1 This high-profile hack has led to a potential fine of 500m for the financial giant and the hacker in question has been charged with five years' imprisonment and over £200, 000 in fines.